A study of knowledge and practice of urban and rural parents regarding Home care of Children during Diarrhoea - Paudel, Sabitri Kumari (2013)
This comparative, exploratory type of study was adopted to measure the knowledge and practice about care of children under five during diarrhoea between Urban and Rural parents for partial fulfillment of requirement for Bachelor degree in Nursing. The objectives of this Study was to compare the knowledge and practice between Urban and rural parents regarding home care of under 5 children during diarrhea. The area of the study was Medical OPD of Kanti Children Hospital.